The nutrition policy process: The role of strategic capacity in advancing national nutrition agendas - Pelletier, David L.; Menon, Purnima; Ngo, Tien; Frongillo, Edward A.; Frongillo, Dominic (SAGE Publications, 2011)
Undernutrition is the single largest contributor to the burden of disease in developing countries and has documented effects on social and economic development, yet progress in reducing undernutrition remains slow. This paper identifies the range of factors that have influenced the nutrition agenda in developing countries, in order to inform the implementation of three major global initiatives related to undernutrition. Data sources include interviews with nutrition practitioners at the national and international level, written accounts from six African countries, and observations of the policy process in five countries. Data were thematically coded to identify recurrent factors that facilitated or inhibited progress in addressing undernutrition. The data reveal the following: First, societal conditions and catalytic events pose a variety of challenges and opportunities to enlarge and shape the nutrition agenda. Some countries have been successful in using such opportunities, while others have been less successful and there have been some unintended consequences. Second, disagreements over interventions and strategies are an almost universal feature of the nutrition policy process, occur primarily among mid-level actors rather than among politicians or senior administrators, and are primarily the product of structural factors such as organizational mandates, interests, and differences in professional perspectives. Third, many of these structural factors can be molded, aligned, and/or circumvented through strategic action on the part of the mid-level actors to strengthen movement on the nutrition agenda. This evidence that strategic action can redirect and/or overcome the effects of structural factors has important implications for future efforts to advance the nutrition agenda.